BS EN 4165-005. Aerospace series. Connectors, electrical, rectangular, modular. Operating temperature 175 °C continuous. Part 005. Stackable mouting receptable 2 and 4 modules, series 3 (5th August 2021) - British Standards Institution,
No abstract available